ACADEMIC INTEGRITY: CHALLENGES OF MODERNITY - Олена Тринус (Вісник Кафедри ЮНЕСКО «Неперервна професійна освіта ХХІ століття», 2020)
In recent years, the Ukrainian academic and educational community has been addressing issues of academic integrity and the implementation of international academic standards. In the civilized academic world, a fundamental role attaches to the fundamental values of academic integrity as an effective instrument for the quality of education ensuring, the moral and ethical image of a modern educator and scientist formation, the creation of a highly competitive society. In the article the essence of the concept "academic integrity" in modern discourse is revealed, and its components are presented. The European experience in counteracting of academic fraud has been analyzed; its most widely used methods are outlined. It has been found that there is no ideal way of counteracting academic abuse in the world; standardized procedures for assessing the educational policy of academic institutions regarding academic integrity have not been developed. The information on the SAIUP project (Strengthening Academic Integrity in Ukraine Project), which was launched in Ukraine to promote academic integrity, has been submitted. The scientific policy of the Ivan Ziaziun Institute of Pedagogical Education and Adult Education for preventing manifestations of academic unfairness is described, as well as the introduction of a system of measures to avoid manifestations of academic plagiarism and selfplagiarism, citation errors, and practice of falsification of scientific research. It is concluded that the views of the academic community on the problems of academic integrity depend to a large extent on the state policy and definition of the system of social values and ethical norms by educational and scientific institutions. The proposals on adherence to academic integrity in Ukraine on the state and institu-tional levels are substantiated.